(3CNHGQ GdcQGe HCNHGQ GdeSLO GdMQGes - (3CMeO Hf eMeO GdCSOj Gdecj GdTGaYj,J (B1066 (3g` s ((3GdMQe Gdeci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa HjJg GdMQGe CeG HYO , agPG JCdja dWja dhGdOiPcQ ajgG eG ai aVd GdHjJ GdTQja hGdWhGa Hg heG LYd dg ai Chdg NWHI edGFeI , hEfeG bGd QJHJg Ydi ebOeI hGdKdGKI ebGUO hNGJeI s
(3BNQgG (B:s
(3hefgG bHQ YHO Gddg Hf YHGS QVi Gddg YfgeG HGdWGFa , hgh eMd eYQha Sei HPdc deG Qhi Cf QLdkG CUGH OekG ef bheg hPdc dOYhI GdNdjd Ydjg GdUdGI hGdSdGe Hbhdg (B"(3? hGQRb Cgdg ef GdKfeQGJ ? hGddg CYde hgPG BNQ eG JjSQ LeYg s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS eJCNQ dCHhGH GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B238 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B81 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B160s
Keywords: (3GdJGQjNs